ASPEK LEGAL MAXIMS TERHADAP TRANSAKSI JUAL BELI DI TIKTOK - Mohammad Zuhurul Fuad (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
The rules of fiqh have an important position in the istinbath ahkam method because they can facilitate the process of determining Islamic law, generalize various legal cases, and provide a more systematic and comprehensive understanding. In addition, the rules of fiqh also play a role in resolving legal problems that have not been stipulated in Islamic legal sources, so that they can be used to provide a consistent interpretation of Islamic law. Along with the development of technology, various new challenges and opportunities have emerged in fatwas. Technological advances have presented various new legal issues, such as those related to information technology, biotechnology, and social media and entertainment. The rapidly growing media and entertainment industry in Indonesia also demands halal regulations, such as those carried out by the Bahtsul Masail Nahdlatul Ulama Institute (LBM NU) of West Java which issued a halal fatwa on media and entertainment products, including buying and selling transactions through the Tiktok application. Based on the explanation that has been done, it can be concluded that the LBM PWNU of West Java is of the opinion that the transactions that occur on the Tiktok Shop are valid as long as they meet the requirements and laws of buying and selling according to the fiqh category. However, this fatwa also recommends the Government to overcome the negative impacts of the Tiktok Shop application. The fatwa of the LBM PWNU West Java is basically irrelevant. This is because the fatwa separates the transactional aspect from the aspect of harm as an impact of the transaction. In the analysis and application of Maqasid Syariah, the Tiktok Shop application which has harm and all the potential harm that follows, then it is appropriate for the application to be deactivated again. This is for the sake of realizing an economy that is beneficial and beneficial for all Indonesian people.